(untitled) (Journal of Dhaka Medical College, 2011)
Context: Stroke is the third commonest cause of death in developed countries and is responsible for the physical disability of a large population. Of two types, ischaemic stroke covers 85% and haemorrhagic stroke is only 15%. Methods: A case control study was designed to see the association of serum vitamin B12 and folic acid level with ischemic stroke. The study was done from January to December 2009 in the Department of Biochemistry, Dhaka Medical College, Dhaka. A total of 60 subjects were selected as study population. Among them 30 were diagnosed case of ischaemic stroke and 30 were age and sex matched healthy control. Results: The mean vitamin B12 and folic acid levels in case group were 231.02±10.81 pg/ml and 2.29±0.54 ng/ml respectively. For control group, the mean vitamin B12 and folic acid levels were 278.72±15.88 pg/ml and 7.24±2.19 ng/ml respectively. Conclusion: The study suggests that low levels of serum vitamin B12 and folic acid are associated with ischaemic stroke. Key words: Ischaemic stroke; vitamin B12; folic acid. DOI: 10.3329/jdmc.v19i2.7080 J Dhaka Med Coll. 2010; 19(2) : 115-117